THE DEVELOPMENT OF A MODEL OF STEM EDUCATIONAL MANAGEMENT IN BAN NONG YAI MUNICIPALITY SCHOOL, OFFICE OF EDUCATION, KHON KAEN MUNICIPALITY - Rodthaisong, Somwang (Journal of Graduate MCU KhonKaen Campus, 2020)
The purposes of this research were to 1) study the components and indicators of STEM Education management in Ban Nong Yai Municipality School, Office of Education, Khon Kaen Municipality 2) study the current conditions and desirable conditions of the STEM Educational administration in Ban Nong Yai Municipality School, Office of Education, Khon Kaen Municipality 3) develop the model of STEM Educational management in Ban Nong Yai Municipal School, Office of Education, Khon Kaen Municipality. The research results are as follows: There are 6 components and 38 indicators of STEM education management in Ban Nong Yai municipality school, Office of Education, Khon Kaen Municipality, as follows: Component 1 : curriculum development consists of 6 indicators. Component 2 : teacher development consists of 7 indicators. Component 3 : learning management consists of 6 indicators. Component 4 : supervision consists of 6 indicators.Component 5:creating the development network consists of 6 indicators. Component 6 : research and development consists of 7 indicators. The overall assessment of the suitability and possibility is at the highest level. The current conditions of the STEM education management in Ban Nong Yai Municipal School, Office of Education, Khon Kaen Municipality, was at a medium level (= 3.40, S.D. = 1.04) and the desirable condition was at a high level ( = 4.49, S.D. = 0.67). According to the measurement and evaluation of the actual situation, the model of STEM education management in Ban Nong Yai Municipal School, Office of Education, Khon Kaen Municipality, called the CTLSCR Model, consists of 6components which are 1) Curriculum Development 2)Teacher Development means inspiring, encouraging teachers to self-study, encouraging teachers to think creatively and design a full educational learning activity, promoting to be the agent of change, creating the professional learning community (PLC), evaluation of STEM teachers and promoting teachers to be selected for outstanding STEM teachers 3) Learning management 4) Supervision and evaluation 5) Create a network of development alliances 6) Research and development.